Solitary Plasmacytoma of Rib Origin in a Young Adult- A Rare CaseReport (Journal of Surgical Sciences, 2019)
Solitary plasmacytoma of bone, specially of a single rib, is a rare disease and is characterized by onlyone or two isolated bone lesions with no evidence of disease dissemination. Here we present a caseof 35-year-old male who was presented with a recurrent swelling in left lower lateral chest wall withsymptoms of localized pain. Radiological evaluation revealed a solitaryexpanding lesion in left lowerlateral chest wall. Fine needle aspiration showed numerous small round cells having hyperchromaticnuclei with scanty cytoplasm. en-bloc resection of the tumor, including involved part of left 9th rib,the intercostal muscle and the parietal pleura with primary closure of chest wall. Histopathology ofthe resected mass revealed plasma cell neoplasm, highly suggestive of solitary plasmacytoma. Thepatient referred to oncologist for further management.Journal of Surgical Sciences (2017) Vol. 21 (1) :39-41